PERANCANGAN DAN IMPLEMENTASI SISTEM PAKAR BERBASIS WEB UNTUK REKOMENDASI JURUSAN KULIAH BAGI SISWA SMAN 6 KABUPATEN TANGERANG. - Adityo, Reza; Kedurang, Afrizzal Pebriansyah; Pratama, Rucci Nabil; Maulana, Arbi; Rafly, Muhammad; Sari, Intan Permata; Farhan, Muhammad Ghalbi; Nazili, Muhammad Haqi; Agustina, Putri (JAMAIKA: JURNAL ABDI MASYARAKAT, 2026)
ABSTRACT The selection of a college major is a crucial decision for high school students and often causes anxiety due to limited self understanding and lack of information about study programs. This community service activity aims to design and implement a web based expert system at SMAN 6 Kabupaten Tangerang to help students choose majors that match their interests, talents, and academic abilities. The implementation method includes needs analysis, system design using the Forward Chaining method, socialization, and training on system usage for students and guidance counseling teachers. The results show that the expert system is able to provide accurate recommendations based on user input. Evaluation through questionnaires indicates an 85 percent increase in students’ understanding in determining their academic career choices.   Keywords: Expert System, Major Recommendation, Web, Community Service, SMAN 6 Kabupaten Tangerang.